Defective metabolism of hypertriglyceridemic low density lipoprotein in cultured human skin fibroblasts. Normalization with bezafibrate therapy. - Kleinman, Y (1985)
The metabolism of hypertriglyceridemic low density lipoprotein (HTG-LDL) was investigated in upregulated cultured human skin fibroblasts. Low density lipoprotein (LDL) was isolated by zonal centrifugation from the plasma of seven HTG subjects, before and 2 wk after the initiation of bezafibrate (BZ) therapy. HTG-LDL is a cholesterol-poor, triglyceride-rich lipoprotein of smaller diameter than BZ-LDL or normal LDL (N-LDL). Binding, cell association, and proteolytic degradation of HTG-LDL were compared with that of BZ-LDL and N-LDL and were found to be significantly lower by a paired t test analysis (P less than 0.001). After 6 h preincubation with unlabeled HTG-LDL, the incorporation of [14C]acetate to sterols was significantly higher than with BZ-LDL or N-LDL (577 +/- 43.7; 330 +/- 41.5; 262 +/- 47, mean +/- SE, picomoles sterols per milligram cell protein per 2 h, respectively; P less than 0.001 by paired t test). To determine the effectiveness of HTG-LDL and BZ-LDL on the down-regulation of LDL receptor activity, up-regulated cells were incubated for 48 h with HTG-LDL and BZ-LDL. LDL receptor activity was significantly higher after preincubation with HTG-LDL compared with BZ-LDL, and the rates of sterol synthesis were similarly increased. These results demonstrate that HTG-LDL does not down-regulate the LDL receptor activity as efficiently as BZ-LDL and that its cholesterol content is not enough to adequately suppress cellular sterol synthesis. Significant correlation between LDL composition and cholesterol synthesis by cultured cells was found with all LDL preparations over a wide range of cholesteryl ester to protein ratio (0.8-2.2). This correlation indicates that the compositional and structural abnormalities of HTG-LDL, and especially the low cholesterol content of the lipoprotein, alter LDL metabolism and cellular cholesterol formation.